Transport of radiative heat transfer in dissipative Cross nanofluid flow with entropy generation and activation energy. (27th August 2019) - Shahzad, M; Sun, H; Sultan, F; Khan, W A; Ali, M; Irfan, M
Abstract: In this paper, features of entropy generation for mixed convective flow of a Cross nanoliquid are discussed. Properties of Hall characteristics for nonlinear mechanisms are elaborated on for greater Loren's force aspects. Thermophoretic and Brownian diffusion effects are taken into account to investigate colloidal analysis for a non-Newtonian fluid. Moreover, a convectively heated surface is considered in the modeling of a physical problem. The modeled problem is simplified through a lubricant procedure. A numerical solution of the proposed physical problem is obtained through a bvp4c scheme. More specifically, we detect that the colloidal property of nanomaterials significantly affects the properties of the base liquid and entropy generation mechanism. Significant features of the Bejan number entropy generation rate are explained via graphical data.